The Effect of using Vocabulary Self-collection Strategy on Students’ Reading Comprehension at SMK N 1 Pangkalan Kerinci - Tengku Zamrizal (Instructional Development Journal, 2024)
The aim of this research to find out the weather there is any significant difference between before and after the use vocabulary self-collection strategy on students’ reading comprehension. The design of the research is a Quasi Experimental Design Nonequivalent Pre-test and Post-test Group Design”. Two groups are served as an experimental group and the other one as compared group Two classes of SMK N 1 Pangkalan Kerinci first-year students make up the research participants. X1 Networking Computer Technique (28 students) served as experimental group 1 and X Accounting Major (28 students) served as experimental group 2. Cluster random sampling was applied. Using SPSS 21 version, the data were analyzed using the paired sample t-test and independent sample t-test formula. The result of the research The analysis showed by using paired sample t test formula. to was -6,669, higher than tt with df 27 in significant 5% and 1% (2.06 <6,669>2,78. Furthermore, it also can be seen that Sig. (2-tailed) or probabilities was 0.000 smaller than 0.05 (0.000<0.05). It means that Ho was rejected and Ha was accepted or there was a significant effect of using Vocabulary Self-collection strategy reading toward students’ reading comprehension of narrative text for experimental group 1. In short, Vocabulary Self-collection help the experimental groups to pay more attention to the target of learning, invest a higher level of ability and mental effort, and engage in a deeper cognitive processing